Stochastic assessment of burst pressure for corroded pipelines - Marques Ferreira, Adriano Dayvson; de Siqueira Motta, Renato; Afonso, Silvana M. B.; Willmersdorf, Ramiro B.; Lyra, Paulo R. M.; de Andrade, Edmundo Q.; Cunha, Divino J. S. (Journal of the Brazilian Society of Mechanical Sciences and Engineering, 2021)
Pipeline wall loss is a major concern of the oil and gas industry. The computational simulation through the finite element method is one of the most efficient and reliable tools to quantify the remaining strength of corroded pipes. This work presents a new procedure and tool for structural integrity assessment of corroded pipelines subject to internal pressure, in which the complex corrosion profile is obtained from field inspections. A system and a methodology which generates automatically finite element models will be presented. These models undergo a nonlinear analysis, and failure pressures are obtained. In the second part of this work, the statistical properties of a set of defect profiles are computed and used to generate thousands of synthetic corrosion defects with realistic properties, and these are used to create finite element models that are submitted to a computational cluster, where the open-source package Calculix is used to do nonlinear analyses of these models in parallel. The results of the analyses are automatically collected, and Monte Carlo simulation is used to calculate some statistics of burst pressure (mean and standard deviation). The main purpose of this work is to present the new methodology, to describe the tool developed to automate the whole process of modelling and analysis of the pipelines with real corrosion profiles and to relate the burst pressure with the average and minimum remaining thickness. To demonstrate the efficiency and flexibility of the methodology we present a case study based on real data.